A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico - Pavón-Vázquez, Carlos J.; de Oca, Adrián Nieto-Montes; Mendoza-Hernández, Andrés A.; Centenero-Alcalá, Eric; Cruz-Padilla, Samuel A. Santa; Jiménez-Arcos, Víctor H. (Zootaxa, 2017)
We describe a new species of Plestiodon in the P. brevirostris group from the Balsas Basin in central Mexico. It is distinguished from the other species in the group by the following combination of traits: supraoculars four; interparietal enclosed posteriorly by parietals; primary temporal present; seventh supralabial usually contacting upper secondary temporal; longitudinal dorsal scale rows around midbody 23–26; Toe-IV lamellae 13–15; limbs not overlapping when adpressed against body; dorsolateral light line extending posteriorly to level of posterior end of anterior fourth of body or beyond; light median line absent in all growth stages; primary lateral dark lines separated medially by six dorsal scale rows and upper half of adjacent row on each side at level of midbody; lower secondary dark line faint at level of neck; and light coloration of supralabials extending ventrally to lip border. Analyses based on DNA sequences of three loci support the distinctiveness of the new species, as well as its sister species relationship with P. ochoterenae. The Environmental Vulnerability Score of the new species places it in the high vulnerability category.